2014
DOI: 10.5539/hes.v4n3p38
|View full text |Cite
|
Sign up to set email alerts
|

Data for Flipped Classroom Design: Using Student Feedback to Identify the Best Components from Online and Face-to-Face Classes

Abstract: Colleges and universities have seen considerable enrollment growth in online courses during the past decade. However, online modalities are not optimal for all subject areas or students. There is growing interest in hybrid, blended, and flipped instruction as a way to incorporate the best of different delivery methods. This study investigates and identifies student preferences for both face-to-face and online learning. Participants were undergraduate students from a mix of freshman, junior, and senior level co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 14 publications
(12 reference statements)
2
33
0
1
Order By: Relevance
“…The fundamentally different outlooks at play in a brick and mortar class versus an online course complicate both. Whereas face-to-face interactions anchor the value of classroom settings, online instructors must look to promote student engagement with a class design structure that precisely specifies activities, assignments, and assessments without unduly sacrificing flexibility, organization, and clear expectations (Crews & Butterfield, 2014;Dixson, 2012). This literature suggests that encouraging students in an online environment to engage the class, as well as each other, fundamentally depends on the design and delivery of the course content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fundamentally different outlooks at play in a brick and mortar class versus an online course complicate both. Whereas face-to-face interactions anchor the value of classroom settings, online instructors must look to promote student engagement with a class design structure that precisely specifies activities, assignments, and assessments without unduly sacrificing flexibility, organization, and clear expectations (Crews & Butterfield, 2014;Dixson, 2012). This literature suggests that encouraging students in an online environment to engage the class, as well as each other, fundamentally depends on the design and delivery of the course content.…”
Section: Discussionmentioning
confidence: 99%
“…The unique milieu of an online class, particularly when framed in terms of orthodox social cognitive or self-determination perspectives, creates situational uncertainties regarding a range of personal and contextual variable (Pekrun, 2006;Artino, 2009). For example, Crews and Butterfield (2014) found that face-to-face interaction significantly affects personal and environmental contextual relationships. If so, for example, then how does the absence of conventionally defined face-time in an online environment affect students' interpretation of the potential and performance of peer assessment opportunities?…”
Section: Setting a Design And Delivery Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…This collaborative discussion on the primary sources may serve as the gateway into the broader topic discussion (Westermann, 2014). Crews and Butterfield (2014) indicated that the most positive impact of face-to-face learning is interaction in class discussions, group problems, and other types of active learning. Bligh (2000) argued that in spite of its criticisms, lecturing is as effective as most other teaching methods as a tool to transmit information.…”
Section: Introductionmentioning
confidence: 99%
“…The flipped course design is different from blended learning in that it combines the face to face and online modes of instruction in teaching and learning proses. Chen et al (2014) and Crews and Butterfield (2014) provide some guidelines for flipped learning course design and development. This study used the models proposed for designing effective flipped classroom for higher education course design.…”
Section: Introductionmentioning
confidence: 99%